PENYULUHAN MANAJEMEN PETERNAKAN AYAM POTONG BAGI MASYARAKAT DESA CAMPLONG II - Sanam, Maxs Urias Ebenhaizer; Utami, Tri; Tophianong, Tarsisius Considus; Manuwolu, Lucy Filipini; Sanam, Viona Mariana Dewi (Jurnal Media Tropika, 2024)
ABSTRACT. Camplong II Village, located in Fatuleu District, Kupang Regency, East Nusa Tenggara, is experiencing challenges with food insecurity and stunting among children, partly due to the long dry season, failed harvests and limited employment opportunities. Community empowerment efforts are important to improve the family economy, which is carried out through Community Service (PkM) with a focus on broiler chicken rearing management. There were 15 participants in the extension activities, who were residents of Camplong II Village. This activity included counseling regarding chicken rearing management, biosecurity and entrepreneurship, which succeeded in increasing the knowledge of group members. The results show an increase in farmers knowledge, facilitating integrated and sustainable business development in the chicken farming sector in Camplong II Village. Keywords: Broiler chicken, Camplong II Village, counseling